THE MAJOR STEROLS OF SARGASSUM VULGARE C. AGARDH INVESTIGATED BY MASS CHROMATOGRAPHY - Halket, J. McK.; Lisboa, Belizário P.; Pinheiro-Joventino, Francisca (Arquivos de Ciências do Mar, 2018)
Increasing interest is being shown in the sterol contents of marine plants (Patterson, 1971 ; Goodwin, 1974) and invertebrates (Patterson et al., 1975) for such reasons as chemo-taxonomic significance, economics and diet. The recent introduction of more effective analytical methods in this area e.g. gas chromatography-mass spectrometry and hydrophobic gel column chromatography (Patterson et al., 1975) are helping to reduce many problems concerning sensitivity, specificity and separating powers which beset earlier workers. It is generally recognized that the brown algae, Phaeophyceae, contain fucosterol as the major sterol component (Ikekawa et al., 1968 ; Patterson, 1971 ; Goodwin, 1974) .